The Worldwide Governance Indicators and Tautology : Causally Related Separable Concepts, Indicators of a Common Cause, or Both? - Langbein, Laura; Knack, Stephen (World Bank, Washington, DC, 2012)
Aggregate indexes of the quality of governance, covering large samples of countries, are widely used in research and in aid policy. Few studies examine the validity of these indexes, however. This paper partially fills this gap by examining empirically the dimensionality of the Worldwide Governance Indicators. The six indexes purportedly measure distinct concepts of control of corruption, rule of law, government effectiveness, regulatory quality, political stability, and voice and accountability. Using standard statistical techniques for testing measurement validity, the analysis concludes that the six indexes do not discriminate usefully among different aspects of governance. Rather, each of the indexes merely reflects perceptions of the quality of governance more broadly. An implication of the findings is that the Worldwide Governance Indicator indexes are frequently misused in research and policy applications, where it is commonly assumed that the indexes provide distinct measures of different aspects of the quality of governance. A further implication is that Transparency International's even more widely-known aggregate index similarly reflects perceptions not only of corruption, as intended, but of the quality of governance more broadly.